Aberrant Phase Separation of FUS Leads to Lysosome Sequestering and Acidification - Trnka, Franziska; Hoffmann, Christian; Wang, Han; Sansevrino, Roberto; Rankovic, Branislava; Rost, Benjamin R.; Schmitz, Dietmar; Schmidt, H. Broder; Milovanovic, Dragomir (Frontiers in Cell and Developmental Biology, 2021)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that leads to the death of upper and lower motor neurons. While most cases of ALS are sporadic, some of the familial forms of the disease are caused by mutations in the gene encoding for the RNA-binding protein FUS. Under physiological conditions, FUS readily phase separates into liquid-like droplets in vivo and in vitro. ALS-associated mutations interfere with this process and often result in solid-like aggregates rather than fluid condensates. Yet, whether cells recognize and triage aberrant condensates remains poorly understood, posing a major barrier to the development of novel ALS treatments. Using a combination of ALS-associated FUS mutations, optogenetic manipulation of FUS condensation, chemically-induced stress, and pH-sensitive reporters of organelle acidity, we systematically characterized the cause-effect relationship between the material state of FUS condensates and the sequestering of lysosomes. From our data, we can derive three conclusions. First, regardless of whether we use wild-type or mutant FUS, expression levels (i.e., high concentrations) play a dominant role in determining the fraction of cells having soluble or aggregated FUS. Second, chemically-induced FUS aggregates recruit LAMP1-positive structures. Third, mature, acidic lysosomes accumulate only at FUS aggregates but not at liquid-condensates. Together, our data suggest that lysosome-degradation machinery actively distinguishes between fluid and solid condensates. Unraveling these aberrant interactions and testing strategies to manipulate the autophagosome-lysosome axis provides valuable clues for disease intervention.